An experimental investigation and flow field analysis on cycling clothing fabrics with grooved surface. (21st November 2022) - Jiang, Wei; Qiu, Jun; Ma, Guoqiang; Weng, Ding; Zhang, Jie; Liu, Lifang
Aerodynamic characteristics of a cylinder covered with smooth fabrics and grooved fabrics were studied with wind tunnel test and numerical simulation, emphasizing on drag attenuation. In the wind tunnel test, the aerodynamic drag of nude cylinder and cylinder covered with fabric was measured. The results show that the drag coefficient of the smooth fabric is almost the same as that of the nude cylinder, however, the fabric with micro-groove structure exerts a distinct characteristic on drag reduction behavior. Based on the results of wind tunnel test, the smooth part of fabric with groove is simplified to smooth surface for numerical simulation. The simulation results of the pressure, vorticity, and turbulent kinetic energy on the grooved surface are presented in comparison with those of the smooth surface to illustrate the drag reduction mechanism. The results indicate that for the grooved surface, the pressure difference between the front and back of the cylinder is smaller, the vortex shedding is inhibited more effectively, and the turbulent kinetic energy is higher compared to those on the smooth surface.